Prevalence and Identification of Enterobacter cloacae from Clinical Samples in Thi-Qar - Mohammed, Noor; Ghali ‎, Sanaa (University of Thi-Qar Journal of Science, 2025)
Enterobacter cloacae is an opportunistic pathogen frequently associated with a wide range of clinical infections. Given the increasing prevalence of this bacterium and the limited information available on its virulence factors in Iraq, further investigation is warranted. This study aimed to analyze various clinical samples, accurately identify the presence of E. cloacae using diverse analytical methods, and confirm the findings through advanced diagnostic systems. A total of 200 clinical specimens were collected from hospitals and diagnostic laboratories in Thi-Qar province. Bacterial identification was carried out using morphological and biochemical methods, as well as automated systems such as API 20E and VITEK-2. Out of the 200 samples, 30 (15%) were confirmed to be E. cloacae. The prevalence showed no significant gender difference, with equal distribution between males and females (50% each). The highest infection rate (40%) was observed in the 20–30-year age group. Blood and wound specimens exhibited the highest isolation rate (33.33%), while stool samples showed the lowest (10%). This study emphasizes the clinical relevance of E. cloacae infections in Thi-Qar, particularly among younger individuals and patients presenting with blood or wound infections. The use of automated diagnostic tools proved essential for accurate bacterial identification.